Numerical Simulation of Static Stress-Strain Relationship and Failure Mode for Freeze-Thaw Concrete - Xiaolin Yang; Genhui Wang; Hongzhao Li; Jiang Fan (Advances in Civil Engineering)
To analyze the causes of failure of cubic concrete test specimens under quasistatic axial compression, microtests and finite element numerical simulation of C40 cubic concrete test specimens were conducted without the freeze-thaw cycle and with 50 freeze-thaw cycles. Based on the analysis of the microstructure of concrete, the variation law of the full curve of stress and strain was analyzed by the uniaxial compression test and the splitting tensile test of concrete. The results show that freeze-thaw damage is mainly caused by the cyclic reciprocating stress of the micropore structure inside the concrete. The peak stress of concrete uniaxial compression and splitting tensile strength gradually decrease with the number of freeze-thaw cycles; the full stress-strain curve tends to shift downward and to the right. Finite element analysis shows that under the quasistatic uniaxial compression loading condition, the stress and strain fields in the test specimens are symmetrically distributed but nonuniform. The plastic deformation of the concrete weakens the nonuniformity of the stress distribution and is closer to the experimental failure morphology.